Circles South East: The First 10 Years 2002-2012. (July 2014) - Bates, Andrew; Williams, Dominic; Wilson, Chris; Wilson, Robin J.
This article describes the first 10 years of the implementation of Circles of Support and Accountability (Circles) in the management of sexual offenders in South-East England by Circles South East (CSE). The Circles of 71 core members are reviewed in detail, with reference to demographic data, offense and sentencing histories, risk assessment data, and considerations regarding Multi-Agency Public Protection Arrangements. A group of 71 comparison subjects who were referred to CSE and deemed suitable for but did not receive the service was identified. Follow-up behaviors of both groups are examined (including all forms of reconviction, breach of orders, and prison recall). Over a comparable follow-up period of 55 months, the incidence of violent and contact sexual reconviction in the comparison group was significantly higher than for the Circles cohort. Comparisons are made between expected and actual levels of sexual reconviction, with the Circles cohort showing lower than expected rate of sexual reconviction but not to a statistically significant degree.